SUSPENSION OF THE SUSPECT IN SAIL RIVER WATER PEKANBARU CITY - Intan Ratna Purba; Budijono Budijono; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study aims to determine the value of suspended solids contained in in the waters of the Sail River. This research was conducted in March-April 2019. Load suspended solid samples were taken from three stations, namely at the upstream part (Station 1), the middle part (Station 2) and the downstream (Station 3). Sampling is done three times, and every 10 days sampling is done. The results obtained are the value of suspended solids content ranging from 68-332 mg/L. Thus the Sail River waters have been contaminated by suspended solids. Keywords: Suspended solids, Sail River